2001
DOI: 10.1073/pnas.261456098
|View full text |Cite
|
Sign up to set email alerts
|

Delayed-onset ataxia in mice lacking α-tocopherol transfer protein: Model for neuronal degeneration caused by chronic oxidative stress

Abstract: ␣-Tocopherol transfer protein (␣-TTP) maintains the concentration of serum ␣-tocopherol (vitamin E), one of the most potent fat-soluble antioxidants, by facilitating ␣-tocopherol export from the liver. Mutations of the ␣-TTP gene are linked to ataxia with isolated vitamin E deficiency (AVED). We produced a model mouse of AVED by deleting the ␣-TTP gene, which showed ataxia and retinal degeneration after 1 year of age. Because the brain ␣-TTP functions in maintaining ␣-tocopherol levels in the brain, ␣-tocopher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
245
3
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 250 publications
(258 citation statements)
references
References 27 publications
9
245
3
1
Order By: Relevance
“…Furthermore, in contrast to the previous study which used 15 months-old mice (Leonard et al, 2002) this study used younger (5 months old) mice and showed α-T deficiency that is very severe starting at a much younger age (5 months old). Another important observation made here is that in spite of the extremely low α-T in the CNS, the young mice do not display ataxia which appears only after 9 months of age (Gohil et al, 2004;Yokota et al, 2001). Thus the development of clinical ataxia in the α-TTP-KO animals has a long latency, possibly due to the presence of unknown mechanisms that sustain normal cerebellar functions in young α-TTP-KO mice whose brains are almost devoid of α-T.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Furthermore, in contrast to the previous study which used 15 months-old mice (Leonard et al, 2002) this study used younger (5 months old) mice and showed α-T deficiency that is very severe starting at a much younger age (5 months old). Another important observation made here is that in spite of the extremely low α-T in the CNS, the young mice do not display ataxia which appears only after 9 months of age (Gohil et al, 2004;Yokota et al, 2001). Thus the development of clinical ataxia in the α-TTP-KO animals has a long latency, possibly due to the presence of unknown mechanisms that sustain normal cerebellar functions in young α-TTP-KO mice whose brains are almost devoid of α-T.…”
Section: Discussionmentioning
confidence: 60%
“…A previous study (Hosomi et al, 1998) indicated higher expression of α-TTP mRNA in the cerebellum compared to that in the cortex suggesting an inverse relationship between α-TTP mRNA expression and α-T concentrations. We also note that Yokota et al, 2001 detected very low levels of α-TTP in brain regions compared to that in liver (Yokota et al, 2001); however α-T concentration in the two organs are very similar, further suggesting a lack of causal relationship between α-TTP expression and whole tissue α-T concentrations. It is also noteworthy that α-TTP was not detected in WT-heart (Yokota et al, 2001) but α-T concentrations in WT-hearts hearts are similar to those of WT-livers (Fig.…”
Section: Tissue α-T Concentrations Are Not Directly Correlated With αmentioning
confidence: 67%
See 3 more Smart Citations